Supply Chain Cases Leading Authors, Research Themes and Future Direction - Hilmola, Olli-Pekka (Springer International Publishing, 2018)
This book provides an overview and analysis of the key publications and authors in the study of supply chain management since its inauguration in the 1980s. Reviewing 1699 published research works and case studies, it is the first to combine and analyse publication data and citations in order to assess the most popular topics and authors, and their effect on the discipline's development. Identifying key scholars and articles throughout supply chain management, the author explores research themes such as the emphasis on sustainability and the environment post-financial crisis, as well as a growing interest in food supply chain case studies. New approaches are identified to increase the number of cases which can be put towards building future research projects.